Komunikasi Interpersonal antara Ustadz dan Santri dalam Menanamkan Nilai-Nilai Akhlak di Pondok Pesantren Al-Ittifaqiah Indralaya - Muslimin Muslimin; Achmad Syarifuddin; Rahmat Hidayat (Jurnal Komunikasi Islam dan Kehumasan (JKPI), 2017)
studying communications in a activity of life, meant so that we earn to do interaction two direction or many direction reciprocally to bear input and also result of. Therefore process tranformasi assess Islami through communications basically aim to to free human being of stupidity, depended, and grind. process of Transformasi assess Islam earn teraktualisasi in family, and also school of pesantren. Maisonette of Pesatren Al-Ittifaqiah represent one of the maisonette of pesantren modern exist in south sumatera provinsi precisely in sub-province of ogan strop district of indralaya. In course of learning and teaching it communications all santri obliged to use Arab Ianguage and English, this matter is meant science to application santri can which in earning in face of epoch challenge. Ustadz represent one who teach theologys in maisonette of pesantren. Besides as builder of ustadz have responsibility as counsellor of santri. Interaction between ustadz with this santri represent form of communication of interpersonal.